Twinkle twinkle little star, I know exactly what you are - Kregenow, Julia (Sourcebooks Jaberwocky, 2018)
Two siblings going to bed describe what stars really are--giant balls of hot, dense gas millions of miles from the Earth--in a book that examines constellations, atmospheric turbulence, and black holes.